2018
DOI: 10.1103/physrevc.98.064319
|View full text |Cite
|
Sign up to set email alerts
|

Isovector and isoscalar proton-neutron pairing in N>Z nuclei

Abstract: We propose a particle number conserving formalism for the treatment of isovector-isoscalar pairing in nuclei with N > Z. The ground state of the pairing Hamiltonian is described by a quartet condensate to which is appended a pair condensate formed by the neutrons in excess.The quartets are built by two isovector pairs coupled to the total isospin T = 0 and two collective isoscalar proton-neutron pairs. To probe this ansatz for the ground state we performed calculations for N > Z nuclei with the valence nucleon… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
20
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 21 publications
2
20
1
Order By: Relevance
“…that, (1), it has been proven that the isovector pairing acting on self-consistent Skyrme-HF mean fields can reproduce rather well the mass dependence of Wigner energy [12] and, (2), it has shown that the isovector and isoscalar pairing correlations coexist for any isovector and isoscalar pairing forces [14,15]. This result is in agreement with the exactly solvable models but at variance with the predictions of standard HFB calculations [17,18].…”
supporting
confidence: 73%
“…that, (1), it has been proven that the isovector pairing acting on self-consistent Skyrme-HF mean fields can reproduce rather well the mass dependence of Wigner energy [12] and, (2), it has shown that the isovector and isoscalar pairing correlations coexist for any isovector and isoscalar pairing forces [14,15]. This result is in agreement with the exactly solvable models but at variance with the predictions of standard HFB calculations [17,18].…”
supporting
confidence: 73%
“…Reproducing the basic features of the complex spectra of these odd-odd nuclei in such reduced spaces provides a strong support to the validity of the present approximation scheme. Besides allowing a comprehension of these nuclei that is much simpler and more intuitive than that provided by the shell model, these calculations confirm the central role of quartetting in N = Z nuclei that had already been evidenced in our previous studies of the even-even systems [7,8,9,10,11,12,22]. With respect to these previous works, it appears even more clearly the role of T = 0, J > 0 quartets.…”
Section: Discussionsupporting
confidence: 85%
“…This has been verified in a recent analysis of even-even nuclei in the sd shell which has evidenced a significant role of T = 0, J = 2, 4 quartets in the low-lying states of 24 Mg and 28 Si [22]. The quartets employed in this analysis have not been constructed variationally, as in the quoted works on pn pairing [7,8,9,10,11,12], owing to the difficulty in applying this procedure in the presence of quartets of various nature. T = 0 quartets have been instead simply assumed to represent the lowest states of 20 Ne (two protons and two neutrons outside the 16 O core).…”
Section: Introductionmentioning
confidence: 68%
See 1 more Smart Citation
“…212 Po= 208 Pb+α [6]. On the other hand, configuration space approaches based on correlated quartet structures were recently proven to describe very precisely the four body correlations induced by the residual nuclear interaction [9][10][11][12][13][14][15][16][17][18][19], in both N = Z and N > Z nuclei. A unified microscopic description of real space α clustering and configuration (shell model) space quartet correlations is an open problem in theoretical nuclear physics.Moreover, in N > Z nuclei, it is necessary to consider the interplay of quartet and neutron pair correla- * Email address: virgil.baran@theory.nipne.ro tions.…”
mentioning
confidence: 99%